In search of a family : the challenge of gangsterism to faith communities on the Cape Flats - MacMaster, Llewellyn L. M. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DTh (Practical Theology and Missiology))--University of Stellenbosch, 2010.